The effect of auditory enrichment on growth performance and stress reaction in broiler chickens - T., Hafizah; Idrus, Zulkifli; Soleimani, Abdoreza Farjam (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
An experiment was conducted to investigate the effects of auditory enrichment by means of classical music and Holy Quran recitation on growth performance, and serum level of corticosterone in broiler chickens. Day-old chicks were subjected to the following treatments from day 1 to day 35: (i) no sound enrichment, as control (C), (ii) exposure to classical music (Vivaldi’s Four Season) (CM), and (iii) exposure to holy Quran recital (Yaseen chapter) (QR). Both sound stimuli were applied 3 hours a day intermittently with a level of 75dB using a multi-player (Panasonic RX-DU10) equipped with speakers (1-way, 2 units of 9cm each). The decibel level of sounds was tested using a digital sound level meter (TECPEL DSL-330). The background noise (fans+chicks sound) in control group was at the level of 65 dB. The CM chicks showed greater weight gain than others on day 7 only. Both CM and QR birds had lower CORT than controls on day 7 but thereafter. It was concluded that exposure to music was beneficial to weight gain during the first week only. Exposure to music or Quran recital can dampen stress response during the first week but not at market age.